NEUROPEDAGOGY – PEDAGOGICAL SCIENCE BASED ON NEUROTECHNOLOGY METHODS - O‘rinova Nargiza Faxriddin qizi (American Journals Publishing, 2023)
The article provides an analysis of the history of neurology, its main stages and achievements aimed at the development of neuropedagogy as one of the modern interdisciplinary directions of pedagogical education development. Based on the mutual communication of pedagogy, psychology and neuroscience, the study of pedagogical processes from the point of view of the brain's response lies. The main methods of neuroscience (EEG, MRI, MEG, TD, etc.) are considered in the directions that are actively developing all over the world.
Keywords: pedagogy, education, neurotechnology,neuropedagogy, neuroscience, interdisciplinary research, education development, brain activity.